Khaṣāiṣ Qāmūs “Mu’jam Aṣ-Ṣiḥḥah” (Indūnīsī-‘Arabī) lī Qism Aṣ-Ṣaydāliyyah wa Qism At-Tagẓiyyah Bi Jāmi’ati Dārussalam Gontor wa Muwāṣafātuhū - Yoke Suryadarma; Achmad Farouq Abdullah; Fitri Setyo Rini (University of Darussalam Gontor, 2019)
Khaṣāiṣ Qāmūs “Mu’jam Aṣ-Ṣiḥḥah” (Indūnīsī-‘Arabī) lī Qism Aṣ-Ṣaydāliyyah wa Qism At-Tagẓiyyah Bi Jāmi’ati Dārussalam Gontor wa MuwāṣafātuhūYoke Suryadarma, Achmad Farouq Abdullah, Fitri Setyo RiniUniversitas Darussalam Gontoryoke.suryadarma@unida.gontor.ac.id, farouqabdullah373@gmail.com, fitrisetro1@gmail.com AbstractDictionaries (Qawāmis and Ma’ājim in Arabic term) were a media for the learning of a foreign language, especially for non-native Arabic learners in Indonesia. They are factual proof of the existence of any language standard, as well as a reference to which people refer to the meaning of the word or the way it is spoken or its synonyms. Therefore, the design of theses Dictionaries in this modern age is undoubtedly. The researcher has tried to design a bilingual dictionary (Indonesian - Arabic) in the field of pharmacy and nutrition for students of the departments of pharmacy and nutrition Faculty of Health Sciences University of Darussalam Gontor (UNIDA Gontor) since the last seven months. The researcher has done the design of a bilingual dictionary, starting from data collection and materials, analysis and evaluation until finishing its design in appropriate time. The researcher called it Mu’jam Aṣ-Ṣihah. Based on this, the researcher in this simple article wanted to come up with something important about the design of this dictionary from the way it is designed, its characteristics and specifications so that it becomes clear to other scholars’ students and other researchers the characteristics and specifications of this dictionary, although it was not yet a perfect product. The researcher has relied on qualitative descriptive methodology by focusing on dictionary design based on lexicography. A detailed statement of the characteristics and specifications of this dictionary is provided in the following pages.Keywords: The specification of the dictionary, lexicography, Mu’jam Aṣ-Ṣihah, Bilingual dictionary.خصائص قاموس